Functional diversity in biters: the evolutionary morphology of the oral jaw system in pacus, piranhas and relatives (Teleostei: Serrasalmidae). (8th May 2019) - Huby, Alessia; Lowie, Aurélien; Herrel, Anthony; Vigouroux, Régis; Frédérich, Bruno; Raick, Xavier; Kurchevski, Gregório; Godinho, Alexandre Lima; Parmentier, Eric
Abstract: Serrasalmid fishes form a highly specialized group of biters that show a large trophic diversity, ranging from pacus able to crush seeds to piranhas capable of cutting flesh. Their oral jaw system has been hypothesized to be forceful, but variation in bite performance and morphology with respect to diet has not previously been investigated. We tested whether herbivorous species have higher bite forces, larger jaw muscles and more robust jaws than carnivorous species. We measured in vivo and theoretical bite forces in 27 serrasalmid species. We compared the size of the adductor mandibulae muscle, the jaw mechanical advantages, the type of jaw occlusion, and the size and shape of the lower jaw. We also examined the association between bite performance and functional morphological traits of the oral jaw system. Contrary to our predictions, carnivorous piranhas deliver stronger bites than their herbivorous counterparts. The size of the adductor mandibulae muscle varies with bite force and muscles are larger in carnivorous species. Our study highlights an underestimated level of functional morphological diversity in a fish group of exclusive biters. We provide evidence that the trophic specialization towards carnivory in piranhas results from changes in the configuration of the adductor mandibulae muscle and the lower jaw shape, which have major effects on bite performance and bite strategy.